Salvia gibbosa, S. gracilicaulis and S. ruizii (Lamiaceae), three new species from Peru - González-Gallegos, Jesús Guadalupe; Uría, Rolando; Rodríguez-Rodríguez, Eric Frank (Phytotaxa, 2024)
Peru is the second American country in terms of species richness of the genus Salvia but such diversity seems to be stabilized when compared with that in other American countries with continuous findings of new Salvia species. This is probably an artifact reflecting the need to intensify the study of the genus in the country and several taxonomic novelties are predicted. In fact, recent botanical explorations in northern Peru have led to the discovery of three new species unmatched with any of the known salvias, which are here consequently supported as new additions to the Peruvian Flora: Salvia gibbosa, S. gracilicaulis and S. ruizii. Descriptions, diagnostic characters, photographs and a distribution map are presented to support the proposal of these new species.